Analisis Proses Berpikir Siswa Dalam Memecahkan Masalah Pada Materi SPLDV Di Kelas IX SMP Negeri 11 Sungai Kakap Berdasarkan Teori Polya - Siti Nuraini; Syarifah Fadillah Al Hadad; Sandie Sandie (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Abstract: This research was conducted at SMP Negeri 11 Sungai Kakap and aims to identify students’ thinking processes in solving problems on the topic of System of Linear Equations in Two Variables (SPLDV) based on Polya’s theory. The research method used is descriptive qualitative, with data collection thecniques consisting of measurement and direct communication. The instruments used were written tests and interviews. The data analysis techniques applied in this study include data reduction, data presentation, and conclusion drawing. Based on the analysis of six students in solving SPLDV problems using Polya”s framework, it can concluded that their thinking processes involve three main forms: assimilation, accommodation, and abstraction. Assimilation is dominant in the stage of understanding the problem, while accommodation tends to increase during pore complex problem-solving phases. Abstraction appears particularly in the stages of planning the solution and reviewing the results. These findings indicate that each student exhibits a distinct pattern of thinking, yet genelary follows the cognitive developmental dynamics aligned with Piaget’s theory. Keywords: Thinking Process, Problem Solving, Polya’s Theory, SPLDV